THE LIBERATION OF AL-QUDS BETWEEN DIVINE DECREE OR HUMAN EFFORT: A HERMENEUTICAL ANALYSIS OF Q.S. AL-MĀ’IDAH [5]: 20–26 - A’azliansyah Farizil Anam; Zahrah Faizatun Nafi’ah; Ilham Nabil Aufa (Sekolah Tinggi Agama Islam Sadra, 2025)
This study is motivated by the urgency of defending al-Quds as a holy city that has a special position theologically, historically, and geopolitically, while also responding to the exclusive claim of Jewish Zionists that it is “The Promised Land,” which is considered to deviate from the moral requirements and justice of revelation. The purpose of this study is to examine the position of al-Quds from an Islamic perspective, trace its history of inclusive management, critique Zionist religious political claims, and offer a relevant strategic framework for liberation in the contemporary era. The research design includes normative qualitative-descriptive research, applying Hans-Georg Gadamer’s hermeneutics, which is relevant to the research topic. It serves to combine the freshness of meaning in the current context from all existing horizons, be it theological-historical narratives, hadith literature, classical-contemporary interpretations, or modern socio-political reasoning. The results of the study show that the sanctity of al-Quds stems from the principle of tawhid and universal Islamic values that prohibit oppression, discrimination, and monopoly of worship spaces, and that the history of the city’s management under Islamic rule is clear evidence of a fair and open governance model for all religious adherents. This study also found that protecting al-Quds relies on human efforts, not divine decree, which requires strategic efforts through diplomacy, civil resistance, international public support, and interfaith solidarity. The study concludes that the liberation of al-Quds must be positioned as a global humanitarian issue, not merely a religious conflict, and requires synergy between internal reform of the Muslim community and external support from the international community to restore its function as a city of peace and a symbol of universal justice.